2005
DOI: 10.1532/hsf.698
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Artery Bypass Surgery May Produce a Hypercoagulable Patient

Abstract: <P>Background: The incidence of thromboembolic events following traditional open heart surgery has not been clinically significant. However, with beating heart surgery, for which cardiopulmonary bypass (CPB) is not required, the incidence of spontaneous intravascular thrombosis may be similar to that encountered after general surgeries. Compounding this risk is that many cases of off-pump coronary artery bypass (OPCAB) surgery are reserved for the elderly patient with multiple comorbidities. The few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Other studies have reported the same trend. Quigley et al (15) have proved clinical evidence of hypercoagulability measured by thromboelastography in patients undergoing OPCAB that exists beyond the first postoperative day. Casati et al (16) have investigated activation of coagulation and fibrinolysis comparing OPCAB and CABG with CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported the same trend. Quigley et al (15) have proved clinical evidence of hypercoagulability measured by thromboelastography in patients undergoing OPCAB that exists beyond the first postoperative day. Casati et al (16) have investigated activation of coagulation and fibrinolysis comparing OPCAB and CABG with CPB.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of significantly increased D-dimer levels in on-pump group B at the end of surgery and the equalization of elevated D-dimer levels between the on-pump and off-pump groups 24 hours after the surgery is in agreement with the findings of others. 10,11) The question of a possibly delayed increase in coagulant and fibrinolytic activity in off-pump surgery arises and slightly controversial clinical conclusions [23][24][25] should warrant further studies. Thromboelastography provides a complete graphical representation of blood coagulation and eventual subsequent lysis of the clot in almost real time.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented the existence of a relative hypercoagulable state after off-pump surgery, associated with higher levels of postoperative platelet activity and a decrease in platelet sensitivity to aspirin after OPCAB. [52][53][54][55][56][57][58][59][60] Moreover, in some early studies of graft patency after OPCAB, vein graft occlusion was noticeably higher both early and late after OPCAB compared with conventional CABG. 53,61 Questions were therefore raised about whether antiplatelet therapy with aspirin alone would be sufficient for patients after OPCAB, and as early as 2003, leading off-pump centers instituted policy changes to treat all OPCAB patients with both clopidogrel and aspirin after surgery for a duration of 3 months.…”
Section: Off-pump Cabgmentioning
confidence: 99%